2014
DOI: 10.1111/hae.12467
|View full text |Cite
|
Sign up to set email alerts
|

New predictive approaches for ITI treatment

Abstract: Summary Immune tolerance induction (ITI) therapy in patients with haemophilia A and inhibitors constitutes a huge burden for affected patients and families and poses a large economic burden for a chronic disease. Concerted research efforts are attempting to optimize the therapeutic approach to the prevention and eradication of inhibitors. The Italian ITI Registry has provided data on 110 patients who completed ITI therapy as at July 2013. Analysis of independent predictors of success showed that, together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
(94 reference statements)
1
8
0
2
Order By: Relevance
“…The two samples negative for anti‐FVIII IgG4 were the initial and final samples from a single patient (H8), who developed anti‐FVIII IgG4 (and was successfully tolerized) in the interim. It has been previously reported that anti‐FVIII IgG4 antibodies are typically observed only in samples with high‐titre inhibitors, whereas low‐titre inhibitors are predominantly anti‐FVIII IgG1‐positive . Our study using the FLI found the vast majority of low‐titre inhibitor samples to be both anti‐FVIII IgG1 and IgG4 positive .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The two samples negative for anti‐FVIII IgG4 were the initial and final samples from a single patient (H8), who developed anti‐FVIII IgG4 (and was successfully tolerized) in the interim. It has been previously reported that anti‐FVIII IgG4 antibodies are typically observed only in samples with high‐titre inhibitors, whereas low‐titre inhibitors are predominantly anti‐FVIII IgG1‐positive . Our study using the FLI found the vast majority of low‐titre inhibitor samples to be both anti‐FVIII IgG1 and IgG4 positive .…”
Section: Discussionsupporting
confidence: 51%
“…antibodies are typically observed only in samples with high-titre inhibitors, whereas low-titre inhibitors are predominantly anti-FVIII IgG1-positive. 22,23 Our study using the FLI found the vast majority of low-titre inhibitor samples to be both anti-FVIII IgG1 and IgG4 positive. 3 Samples from subjects H9, H10 and H11 show the value of performing additional testing in questionable cases.…”
Section: Discussionmentioning
confidence: 79%
“…The correlation between inhibitor and IgG4 were r* 0.949, r* 0.803, r* 0.866, patients 2, 3 and 5 respectively (*Spearman correlation). discussion regarding the better success rates when FVIII concentrates containing VWF is used in ITI protocols [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, ITI is a complex and often longlasting therapy, involving a fair amount of human and material resources. Inhibitor titers measured by the Nijmegen-Bethesda assay are the most important parameter for ITI management, thus, the accuracy of this assay can be regarded as a critical determinant of ITI success [6]. In this study, we demonstrated that heat treatment of plasma samples improved the sensitivity of the Nijmegen-Bethesda method, particularly in patients who were recently exposed to FVIII concentrates, as during ITI treatment.…”
Section: Discussionmentioning
confidence: 76%